Genetic variability, heritability and genetic advance in bottle gourd [(Lagenaria siceraria (Mol.) standl.] (Indian Journal of Arid Horticulture, 2025)
Extent of variability, heritability and genetic advance of fruit yield and its contributing characters were estimated in twelve diverse genotypes of bottle gourd. The study indicates that there is considerable amount of genetic variability for all the characters studied. The length of edible green fruit exhibited highest value of genotypic and phenotypic coefficient of variations (GCV and PCV). High estimates of heritability, genotypic coefficient of variations and genetic advance as per cent of mean were observed for length of edible green fruit, number of fruits plant' and weight of edible green fruit. This indicates that these characters in bottle gourd can effectively be improved through selection.
Keywords: Bottle gourd; heritability; genetic advance